Consequences of peace the Versailles settlement, aftermath and legacy - Sharp, Alan 1943- (Haus histories, 2011)
"Consequences of Peace: The Versailles Settlement - Aftermath and Legacy". This final volume in the Paris Peace Conference series will evaluate the immediate and later effects of the last great peace gathering which sought to settle the world's affairs at a stroke something that was not attempted after either the Second World War or the Cold War. The Versailles settlement has not enjoyed a great reputation. It has been blamed for causing a second major conflict within a generation, thus apparently fulfilling Marshal Foch's gloomy prediction that this is not a peace, it is an armistice for twenty years'. More recently commentators have suggested that the post-1989 ethnic disturbances in the Balkans and on the fringes of the former Soviet Union are the old chickens of Versailles coming home to roost'. The contemporary world still struggles to come to terms with the implications of President Woodrow Wilson's troublesome principle of national self-determination, and remains embroiled in the ambiguities and complexities of the Middle East, an area for whose boundaries and problems the Great War and settlement bear significant responsibility.